ANALISIS PERUBAHAN URBAN HEAT ISLAND MENGGUNAKAN CITRA LANDSAT 8 TAHUN 2014 DAN 2019 (STUDI KASUS DAERAH JAKARTA SELATAN) - Tutut Rachmawati (Jurnal Geodesi UNDIP, 2021)
As the capital of the State of Indonesia, Jakarta is also the largest central city with all the activities in it with a population per 2019 reaching 10.5 million according to the Central Statistics Agency. Many of its activities leave a carbon footprint as one of the contributors to Urban Heat Island, a minimum of 456.420 tons / km, and a maximum of 2.053.248 tons / km for 2014, and a minimum of 638.239 tons / km and a maximum of2.731.801 tons / km in 2019 based on the Carbon Footprint method using DKI Jakarta sectoral statistics. From these results, it was obtained an analysis of the increase in the temperature of the Land Surface Temperature in Landsat8 imagery from 2014 to 2019 amounting to 0.8 ° and an increase in the value of Urban Heat Island by 2 ° c. If this phenomenon continues, these values will increase so that the earth's temperature cannot be controlled. This research is handled as an illustration of society to save carbon energy and for the government as an effort to prevent disasters in urban areas.